2022
DOI: 10.1021/acs.est.2c00957
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Hepatotoxicity of a Novel Perfluoroalkyl Ether Sulfonic Acid, Nafion Byproduct 2 (H-PFMO2OSA), and Legacy Perfluorooctane Sulfonate (PFOS) in Adult Male Mice

Abstract: Nafion byproduct 2 (H-PFMO2OSA) has been detected in the environment, but little is known about its toxicities. To compare the hepatotoxicity of H-PFMO2OSA with legacy perfluorooctane sulfonate (PFOS), male adult mice were exposed to 0.2, 1, or 5 mg/kg/d of each chemical for 28 days. Results showed that, although H-PFMO2OSA liver and serum concentrations were lower than those of PFOS, the relative liver weight in the H-PFMO2OSA groups was significantly higher than that in the corresponding PFOS groups. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…17,51 Notably, hepatomegaly is a common indicator of PFAS-induced hepatotoxicity. 5,46,52,53 According to the US EPA, the lowest observed adverse effect levels (LOAEL) for increased relative liver weights in male CD1 mice following gavage exposure to HFPO-DA are 3 mg/ kg/d (28 d) and 5 mg/kg/d (90 d). 41,54 These levels are higher than the LOAEL (0.5 mg/kg/d) observed in our study after 7 days of HFPO-DA exposure, suggesting a potential underestimation of HFPO-DA-induced liver toxicity.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,51 Notably, hepatomegaly is a common indicator of PFAS-induced hepatotoxicity. 5,46,52,53 According to the US EPA, the lowest observed adverse effect levels (LOAEL) for increased relative liver weights in male CD1 mice following gavage exposure to HFPO-DA are 3 mg/ kg/d (28 d) and 5 mg/kg/d (90 d). 41,54 These levels are higher than the LOAEL (0.5 mg/kg/d) observed in our study after 7 days of HFPO-DA exposure, suggesting a potential underestimation of HFPO-DA-induced liver toxicity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The liver serves as a crucial metabolic organ and a primary target for PFAS, which can accumulate in hepatic tissue and induce hepatotoxicity. , Notably, hepatomegaly is a common indicator of PFAS-induced hepatotoxicity. ,,, According to the US EPA, the lowest observed adverse effect levels (LOAEL) for increased relative liver weights in male CD1 mice following gavage exposure to HFPO-DA are 3 mg/kg/d (28 d) and 5 mg/kg/d (90 d). , These levels are higher than the LOAEL (0.5 mg/kg/d) observed in our study after 7 days of HFPO-DA exposure, suggesting a potential underestimation of HFPO-DA-induced liver toxicity. Possible factors contributing to the higher LOAEL values for chronic HFPO-DA exposure may include variances in mouse strains used in experiments or an increased resilience to HFPO-DA in mice stemming from prolonged exposure, leading to an eventual recovery from acute hepatic damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That hydro‐PS acid ranked low for PPARα agonism suggests that CAR, PXR and perhaps RXR may be the drivers for its toxicity in rodents. The finding that 28‐day exposure to hydro‐PS acid causes severe hepatomegaly, higher serum bile acids and elevated markers of liver damage in male mice (Wang et al, 2022, 2023), and liver inflammation and high serum bile acid metabolites in pregnant rats (Conley, Lambright, Evans, Medlock‐Kakaley, et al, 2021) suggests that maternal metabolic derangements could contribute to the developmental toxicity of hydro‐PS acid. The relationship of these findings to the developmental toxicity of PFAS remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The PFOS-like substances were designed to be less toxic in organisms, though our knowledge of their biosafety remains limited. So far, the vast majority of the research on the toxic effects of PFOS-like substances pertains to Cl-PFESAs, particularly 6:2 Cl-PFESA, which consistently suggests that 6:2 Cl-PFESA is potent to cause strong detrimental effects on endocrine functions (e.g., thyroidal and lipid steatosis) in organisms as PFOS, or even stronger. The only study to look into the toxicity of Cl-PFOS reported its potential to elicit comparable hepatotoxicity to PFOS in zebrafish larvae . As the recently identified reductive transformation product of 6:2 Cl-PFESA, information about 6:2 H-PFESA is heavily sparse.…”
Section: Introductionmentioning
confidence: 99%